General principles of coercive medical measure application: concepts and basic criteria - A. M. Yashсhenko (Law and Safety)
The article is devoted to the study of the general principles of coercive medical measure application and formulation of the author's own generalized conclusions on this basis, aimed at further development of the scientific idea of such coercive measures of criminal law impact personalization and improvement of their practice implementation through compliance of law enforcement entities with certain rules or criteria. It has been noted that one of the shortcomings of the general principles regulatory certainty of coercive medical measures application is that the current criminal legislation of Ukraine does not have an article that would separately enshrine such general principles or rules. In this regard, the author has proposed own definition of general principles of coercive medical measures application concept and a variant of its regulatory definition in a separate article of the current criminal legislation of Ukraine.